Graphic technology. Prepress digital data exchange using PDF. Complete exchange of printing data (PDF/X-6) and partial exchange of printing data with external profile reference (PDF/X-6p and PDF/X-6n) using PDF 2.0 Part 9, (1st December 2020) - British Standards Institution,
No abstract available